Inhibitory synaptic plasticity - Woodin, Melanie A.; SpringerLink (New York Springer, 2011)
Since its discovery and first publication in 1973, synaptic plasticity in its most popular form -- the plasticity of excitatory glutamatergic synapses -- has been widely investigated. But to fully understand how brain functions develop and are maintained, there is a need for studying the interaction between the different forms of plasticity. Inhibitory Synaptic Plasticity integrates studies that have examined the induction, expression and functional role of inhibitory synaptic plasticity at different organizational levels (from the neuron to the circuit), through four main parts: Refinement, Addiction, Pain & Injury, and Learning & Memory. This volume brings together a large portion of the current thinking about the plasticity of inhibitory synapses, and will foster new ideas and hypotheses for the study of brain circuits and their function.
Refinement. The many faces of inhibitory plasticity: adding flexibility to cortical circuits throughout development.Long-term modification at inhibitory synapses in developing visual cortex. Molecular Mechanism of Long-Term Plasticity at Cerebellar Inhibitory Synapses. Inhibitory plasticity and auditory function -- Addiction.VTA GABAergic Plasticity: An Inhibitory Synaptic Model of Drug Addiction.Midbrain Dopamine Neurons: Implications for the Development of Alcohol-Seeking Behaviors -- Pain and Injury.Mechanisms of plasticity of inhibition in chronic pain conditions.Injury induced epileptogenesis: Contribution of active inhibition, disfacilitation and deafferentation to seizure induction in thalamocortical system. Cellular Mechanisms of Neuronal Cl- Homeostasis and its Modulation by Neuronal Injury -- Learning and Memory.Activity-Dependent Inhibitory Synaptic Plasticity Mediated by Chloride Regulation.Endocannabinoid mediated long-term depression at inhibitory synapses.Inhibitory Synaptic Plasticity & Neurotrophins.
Electronic reproduction.
Keywords: Synapses; Neuroplasticity; Electronic books